2011
DOI: 10.1002/crat.201100206
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oxygen partial pressure on physical properties of nano‐crystalline silver oxide thin films deposited by RF magnetron sputtering

Abstract: Nano-crystalline silver oxide films were deposited on glass and silicon substrates held at room temperature by RF magnetron sputtering of silver target under different oxygen partial pressures. The influence of oxygen partial pressure on the structural, morphological, electrical and optical properties of deposited films was investigated. Varying oxygen partial pressure during the sputter deposition leads to changes of mixed phase of Ag 2 O and Ag to a single phase of Ag 2 O and to AgO. The X-ray diffraction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…In RF magnetron sputtering, the physical properties of the deposited thin films critically depend on the sputter parameters such as oxygen partial pressure, substrate temperature, and substrate bias voltage, sputtering pressure and sputter power. The influence of oxygen partial pressure on the structural, electrical, and optical properties of silver oxide films formed by RF magnetron sputtering was earlier reported [28]. In the present investigation, nanocrystalline Ag 2 O films were deposited on glass and silicon substrate by RF magnetron sputtering at different substrate temperatures.…”
Section: Introductionmentioning
confidence: 51%
“…In RF magnetron sputtering, the physical properties of the deposited thin films critically depend on the sputter parameters such as oxygen partial pressure, substrate temperature, and substrate bias voltage, sputtering pressure and sputter power. The influence of oxygen partial pressure on the structural, electrical, and optical properties of silver oxide films formed by RF magnetron sputtering was earlier reported [28]. In the present investigation, nanocrystalline Ag 2 O films were deposited on glass and silicon substrate by RF magnetron sputtering at different substrate temperatures.…”
Section: Introductionmentioning
confidence: 51%
“…On the other hand, Ag 3d peaks and the atomic percentage of Ag (Figure C) revealed that more AgNPs were exposed on Ag@PDA-5 than on Ag@PDA-2.5. The Ag 3d 5/2 and Ag 3d 3/2 peaks of Ag@PDA-2.5 and Ag@PDA-5 were found at 367.5–367.8 eV and 373.5–373.8 eV, respectively, which could be attributed to Ag 2 O. These results indicate that the AgNPs on Ag@PDA-2.5 and Ag@PDA-5 consist of Ag 2 O. It was interesting that significantly more AgNPs were exposed on Ag@PDA-5 than on Ag@PDA-2.5, while the amount of Ag + released from Ag@PDA-5 and Ag@PDA-2.5 was approximately the same (Figure E).…”
Section: Results and Discussionmentioning
confidence: 80%
“…HR-XPS spectra of (a) Nb 3d of Nb 2 O 5 /Cu, (b) O 1s of Nb 2 O 5 /Cu; Nb and O spectra for Nb 2 O 5 /Ag and Nb 2 O 5 /Ca are shown in Figures S14 and S15, (c) Nb 3p/Ag 3d of Nb 2 O 5 /Ag, (d) Cu 2p of Nb 2 O 5 /Cu, and (e) Ca 2p of Nb 2 O 5 /Ca …”
Section: Resultsmentioning
confidence: 99%